(untitled) (CIPEEX, 2024)
THE OBJECTIVE OF THIS PROJECT IS TO USE THE NET PROMOTER SCORE (NPS) METRIC AS A BASIS FOR DEVELOPING AN ONLINE TOOL THAT AIMS TO MEASURE USERS’ INTEREST AND SATISFACTION WITH PRODUCTS, PLACES AND SERVICES. THIS ONLINE PLATFORM IS DESIGNED WITH AN INTUITIVE AND FRIENDLY INTERFACE WITH THE MAIN OBJECTIVE OF CLARIFYING USERS’ DOUBTS ABOUT RELEVANT PRODUCTS, PLACES OR SERVICES. TO ENSURE A PERSONALIZED APPROACH, WE AIM TO IMPLEMENT NPS SURVEYS THAT CAN BE ADAPTED TO THE SPECIFIC CONTEXT OF EACH ASSESSMENT. THE PLATFORM USES ONLINE DATA COLLECTION TOOLS AND ONLINE SURVEY SYSTEMS TO COLLECT USER RESPONSES. FURTHERMORE, WE USE ADVANCED STATISTICAL ANALYZES USING SPECIAL SOFTWARE SUCH AS EXCEL, SPSS, R OR PYTHON. THESE ANALYZES INCLUDE, AMONG OTHERS, STATISTICAL METHODS TO ASSESS THE SIGNIFICANCE OF RESULTS, REGRESSION ANALYSIS, CLUSTER ANALYSIS. OUR GOAL IS TO PROVIDE VALUABLE AND ACCURATE INSIGHTS THAT HELP YOU CONTINUALLY IMPROVE RELEVANT PRODUCTS, PLACES AND SERVICES.